DETERMINANT FACTORS THAT INFLUENCE FAMILY BEHAVIOR IN CARING FOR LBW USING THE HEALTH PROMOTION MODEL APPROACH - Miliasari, Ethi; Rahayu, Elmi Aris (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
LBW care in the NICU room causes separation between babies and parents for quite a long time, so that parents of LBW often lack support and opportunities to be involved in care while in the NICU. Based on this description, it is necessary to develop a structured health education model for LBW families. This education is based on determinant factors that can influence the behavior of LBW families, so that it can improve the quality of life of LBW and the quality of nursing services. Objective: To identify factors that influence family behavior in caring for LBW in the NICU using the HPM approach. Method: This type of research is explanatory , the research design is cross sectional . The research sample was 105 families with LBW who were treated in the baby room of RSUD Dr. Soetomo Surabaya, data were analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) test. Results and Analysis: Perceived benefits have an effect on commitment (t statistics value = 3,790 > 1.96 ) , perceived obstacles have a significant effect on commitment (t statistics = 2,330 > 1.96), Perceived Self Efficacy has an effect on commitment (t statistics value = 3,370 > 1.96), commitment influences family behavior of LBW (t statistics value = 6,204 > 1.96). Discussion and conclusions Personal factors including age, marital status, education and income of LBW parents do not influence perceived benefits, perceived barriers, perceived self-efficacy and interpersonal influence. Perceived benefits, perceived barriers, and perceived self-efficacy influence family commitment in caring for LBW. Interpersonal influence does not affect commitment. Commitment influences the behavior of LBW families